Duchenne muscular dystrophy in South Africa : molecular aspects - Ballo, Robea (Division of Human Genetics, 2023)
Robea Balle, Department of Human Genetics, MRC Unit for Skeletal Disorders, UCT Medical School, Observatory, Cape Town, South Africa. Duchenne muscular dystrophy (DMD) is a lethal X-linked neuromuscular disorder, characterised by progressive muscle wasting and weakness. DMD has its onset in early childhood, leading to physical handicap by the mid-teens and usually death by the age of twenty years. Becker muscular dystrophy (BMD) is the allelic form of DMD and is differentiated by its age of onset and milder phenotype. DMD and BMD are incurable and the most effective way of managing affected families is by preventing the recurrence of the di9order. The use of intragenic and closely linked flanking markers facilitates the identification of the defective X chromosome in female carriers and their affected male foetuses. DMD is thought to be the most common of the heritable muscle disorders, having an incidence of l in 3 300. When extrapolated to the large South African population, it presents a significant socioeconomic problem. For this reason, it was decided to develop a molecular genetic service for carrier identification and diagnostic predictions. The first step in the South African study involved the collection of biological material from affected individuals. In so doing, minimum prevalence's in the four major ethnic groups of Black, Caucasian, Indian and Mixed ancestry, were established. Although ascertainment was incomplete for a number of reasons, a markedly increased DMD frequency in the Indian population and a low frequency in the Black population was apparent. In the Caucasian group, an unexpectedly high BMD frequency, compared to DMD, was observed. 110 males affected with DMD and 18 with BMD were screened for deletions using genomic and cDNA probes and multiplex polymerase chain reaction (PCR) technology. Deletions were detected in the dystrophin gene of 47 DMD and 6 BMD patients, occurring predominantly in the 3' region of the gene (65%) and to a lesser extent in the 5' region of the gene (287.). The deletion frequency within individual ethnic groups,